Financial innovation and international debt problems - Dieter Bender (Intereconomics, 1989)
Finaciial innovations are viewed almost universally as a new dimension in international debt management. The following article analyses the direct and indirect effects of using various types of new financial instrument to ease the debt burden. It considers the question whether new forms of international debt management might increase the effectiveness of debt relief programmes and examines specifically whether financial innovations such as debt-equit sswaps, debt-bond swaps and similar arrangements at the level of intergovernmental debtor-creditor relations can help overcome international debt problems.
Keywords: 330; Indebtedness